Assessing impact: a study of India's vaccine preventable diseases - Sharma, Ankita; Sharma, Somya; Sharma, Divyansh (International Journal Of Community Medicine And Public Health, 2025)
The universal immunization programme (UIP) is one of the most cost-effective methods to enhance public health. It is administered by the national rural health mission under the aegis of the ministry of health and family welfare. Despite India's 50-year history of vaccines, vaccine-preventable diseases (VPDs) still cause over 5,00,000 fatalities annually. The present study assesses the UIP 's success in decreasing VPDs in India. The data from 2006 to 2018 was taken from Indiastat.com. Since the research aimed to assess the success of UIP across India, achievements under UIP for each vaccination, i.e., Bacillus Calmette-Guerin; oral polio vaccine-1, 2 and 3; diphtheria pertussis tetanus-1, 2 and 3 and measles, was compared with the cases and deaths owing to the diseases; as per NRHM division and health index (4th round) scores given by NITI Aayog, separately. Data analysis was conducted in MS excel (2019 version). Vaccination achievements varied significantly as per NRHM and NITI Aayog health index, with HFSNNE and MI regions outperforming each other’s. Cases of polio and tetanus were lowest in HFSNE and LI states. Deaths due to diphtheria and measles, mirrored regional disparities with NHFSL and NI states having higher burden. To reduce mortality due to VPD in children, enhancing reporting networks and cross-border cooperation in vaccination strategies are crucial. Policy recommendations include targeted interventions, educational campaigns, infrastructure improvements, incentives, monitoring, evaluation strengthening, policy flexibility, community engagement, capacity building, research, and a phased implementation plan.